Timing of Stressful Life Events Affects Stability and Change of Neuroticism. Issue 2 (March 2014) - Riese, Harriëtte; Snieder, Harold; Jeronimus, Bertus F.; Korhonen, Tellervo; Rose, Richard J.; Kaprio, Jaakko; Ormel, Johan
Neuroticism is a predictor of many health problems. To study the determinants of within–subject change in neuroticism, three hypotheses were tested: (i) subjects who experienced stressful life events (SLEs) show an increase in neuroticism; (ii) high baseline neuroticism moderated this effect; and (iii) recent SLEs had a greater impact on neuroticism than distant SLEs. Data came from the Finnish Twin Cohort. Neuroticism data were collected in 1975 and 1981 and SLEs data in 1981 (n = 21 085). By entering baseline neuroticism as a predictor for neuroticism at follow–up, the outcome measure was change in neuroticism. Changes in neuroticism were predicted from SLE indices or their interaction with baseline neuroticism. Timing of SLEs was taken into account by distinguishing recent from distant SLEs. To control for confounding by shared genes and environments, both within–twin pair and between–twin pair effects were tested for monozygotic and dizygotic twin pairs separately. Neuroticism's six–year stability was high (r = .58, p < .001). Exposure to SLEs modestly increased neuroticism (βs > .55, ps < .001), unconfounded by shared genes. This effect was not moderated by high baseline neuroticism. Recent SLEs (.09 < βs < .15) had more impact than distant SLEs (.03 < βs < .11; ps < .01). In conclusion, the findings strongly supported a model of environmentally driven SLEs causing dynamic fluctuations around a person's set point of neuroticism. Copyright © 2013 John Wiley & Sons, Ltd.